2019
DOI: 10.3389/fnhum.2019.00072
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Modulation of Corticospinal Excitability in Drug-Free Patients With Major Depressive Disorder: A Theta-Burst Stimulation Study

Abstract: Impaired neural plasticity may be an important mechanism in the pathophysiology of major depressive disorder (MDD). Coupled with electromyography (EMG), repetitive transcranial magnetic stimulation (rTMS) is a useful tool to evaluate corticospinal excitability and cortical neuroplasticity in living humans. The goal of this study was to compare rTMS-induced cortical plasticity changes in patients with MDD and in healthy volunteers. In this single-blind controlled study, 11 drug-free patients with MDD and 11 mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…This registration method has previously been used in research studies performed using the same centre's technology. [4,7,18]…”
Section: Comparative Methodsmentioning
confidence: 99%
“…This registration method has previously been used in research studies performed using the same centre's technology. [4,7,18]…”
Section: Comparative Methodsmentioning
confidence: 99%
“…We achieved our a priori sample size estimations (30) based on data from previous studies. To detect a medium to large-sized effect for cortical plasticity (η 2 = 0.12) with a power of 80% and a significance level of 0.025 (Bonferroni corrected), we needed a sample size of minimal 7 subjects per group (patient and control groups) (7,8). To detect a large-sized effect for cortical inhibition (SICI: η 2 = 0.22; CSP: d = 1.02) with a power of 80% and a significance level of 0.025, we needed a sample size of minimal 7 and 17 subjects per group, respectively (18).…”
Section: Subjectsmentioning
confidence: 99%
“…In addition, due to its shorter duration and low stimulus intensity, the iTBS paradigm is less demanding than PAS and therefore more suitable to use in severely depressed patients. Vignaud et al (8) showed impaired cortical plasticity upon iTBS in MDD treatmentresistant patients, although they observed high variability in the response to iTBS. There are only a few studies of cortical plasticity in MDD patients, in which the effect of psychoactive drug use and the variation in depression severity has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations